การสำรวจกลยุทธ์การพัฒนาทักษะการคิดเชิงวิพากษ์ในตัวผู้เรียนภาษาอังกฤษระดับมัธยมศึกษาตอนปลาย - ลิ้มสุคนธ์ ภัคศฬัญศ์; มีศรี ราเชน (An Online Journal of Education, 2018)
This study was conducted to 1) investigate the strategies upper secondary EFL teachers in Thailand use to develop students’ critical thinking skills 2) examine the types of questions asked by upper secondary EFL teachers in Thailand and 3) identify barriers that prevent upper secondary EFL teachers in Thailand from using teaching methods that develop critical thinking skills. Thirty upper secondary EFL teachers from Thai institutions were recruited to complete a self-administered survey designed to gather information about teaching approaches, questioning strategies, and obstacles to teaching critical thinking skills. Their responses indicate that 1) they use various strategies to develop critical thinking skills with questioning being the most commonly used method, 2) they use a variety of questioning techniques to encourage higher-order thinking at least some of the time with questions designed to promote analysis being the most preferable, and 3) a number of barriers limit the ability of upper secondary EFL teachers to teach and assess critical thinking skills, with the most significant barrier being lack of training.